A WALK-IN TYPE CALIBRATION CHAMBER FACILITY FOR 222Rn MEASURING DEVICES AND INTER-COMPARISON EXERCISES. Issue 4 (29th October 2019) - Trilochana, S; Somashekarappa, H M; Kumara, K Sudeep; Mohan, M P; Nayak, S Rashmi; D'Souza, Renita Shiny; Kamath, Srinivas S; Sahoo, B K; Gaware, J J; Sapra, B K; Janik, M; Al-Azmi, Darwish; et al.
Abstract: A walk-in type 222 Rn calibration chamber of volume 22.7 m 3, which has traceability to international standards, is established at the Centre for Advanced Research in Environmental Radioactivity, Mangalore University, India. It has a human–machine interface communication system, a programmable logic controller and sensor feedback circuit for controlling and data acquisition of relative humidity ( RH ) and temperature ( T ). An innovative method for the generation of desired 222 Rn concentration (a few hundred Bq m −3 up to about 36 kBq m −3 ) using soil gas as a source was adopted. Leak rates of 222 Rn from the chamber for the mixing fan ON and OFF conditions were determined to be 0.0011 and 0.00018 h −1 respectively. With the exhaust system fully turned on, the maximum clearance rate of the chamber was 0.58 ± 0.07 h −1 . Excellent spatial uniformity in 222 Rn concentration in the chamber was confirmed (with a mean value of relative standard deviation < 12%) through measurements at 23 locations using CR-39 film-based passive devices. Demonstration of calibration applications was performed using charcoal canister and PicoRad vials as the 222 Rn adsorption devices. The study shows that gamma spectrometry is a convenient alternative approach to liquid scintillation analysis of PicoRad vials for 222 Rn measurement.